Dynamic Trust and Security Management Protocol For Delay Tolerant Networks using Information centric-Networks Architecture (International Journal of Engineering and Computer Science, 2015)
Trust management in mobile wireless network is always been challenging because of frequently changing network environment. This will cause delay tolerance networks (DTN) a high latency, frequent disconnection over unreliable wireless links. To avoid these anomalies we proposed Dynamic Trust and Security Management Protocol (DTSMP).In the current Internet architecture (IP-based architecture), data are treated as network elements as a series of bytes that have to be transferred from a specific source to a specific destination. But the network elements have no knowledge of the information they transfer a, hence cannot realize optimizations that would be possible (e.g., information replication at various points, information-aware traffic engineering, smart in-network caching). To overcome these issues we use the Information Centric-Networks (ICN) architecture for our proposed DTSM protocol. We design and validate the Dynamic Trust and Security Management protocol for delay tolerant networks (DTN) for better optimized secure routing in DTN environment; this includes well-behaved, selfish and malicious nodes. Proposed work is analyzed and validated via extensive simulation. Our protocol determine and apply the best optimized operational setting at the runtime in response to dynamically changing network environment, by will minimize the trust bias and maximize the routing performance. We do comparative analysis with other trust protocols like Bayesian trust-based protocol, DTSM protocol (proposed) with IP-based architecture and DTSMP protocol (with ICN architecture). The results demonstrate that DTSM protocol is able to deal with selfish behavior, malicious, and unreliable nodes. It also shows that our DTSM protocol work efficiently on INC architecture which improve the performance of our protocol. Furthermore proposed protocol can deal effectively with message overhead and message delay which will increase the significant gain in delivery ratio.